Combined laser assisted treatment for permanent hair removal for skin types I‐V with Alexandrite 755 nm and ND:YAG 1064 nm lasers. Issue 1 (16th December 2020) - Zerbinati, Nicola; Protasoni, Marina; Dalla Gasperina, Daniela; Coricciati, Luigi; Mezzana, Paolo; Sbano, Paolo; Greco, Maurizio; D'Este, Edoardo; Rodighiero, Eleonora; Satolli, Francesca
Abstract: This retrospective cohort study regarding hair removal procedures considers all the data collected in three different clinical centers from 2017 to 2019. The device used to perform the treatments was composed of an Alexandrite 755 nm and an Nd:YAG 1064 nm laser, that delivered both wavelengths in a blended simultaneous emission (Thunder MT, Quanta System, Samarate, Italy). The improvement evaluated after five sessions of treatment by an external referee was: 83.0% for armpits, 82.1% for the bikini line, 82.2% for legs, 79.6% for thorax, and 81.6% for the back. The collected temporary skin reaction data reported in this study were all acceptable and transitory resolving in less than 1 week. The level of erythema and perifollicular edema were all signs of the reached treatment endpoint. First degree burns, hyper, and hypopigmentation were also reported in a few cases but these, all resolved before the follow‐up visit without any permanent skin effects. No adverse effects were thus reported to have happened. This retrospective study demonstrates the efficacy of combining Alexandrite and Nd:YAG lasers in a mixed modality with simultaneous emission. This technology permitted to treat patients with skin types I‐V without any reported permanent side effects and with a high pain tolerability compared to the use of Nd:YAG in single mode.